IMPACT OF DEMOGRAPHIC VARIABLES ON BLOOD PRESSURE AND GLYCEMIC CONTROL - Venkataraman, Rajesh; Mathai, Jeethu M; Thomas, Linu; James, Mathew (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was designed to analyse the impact of demographic variables on blood pressure and glycaemic levels in patients with diabetes and hypertension. Methods: A community-based prospective observational study was conducted over a span of six months in the rural villages of Nagamangala Taluk, Mandya Dist, Karnataka. Results: Among 320 subjects, 285 patients had been enrolled in the study. The demographic variable such as age was found to be significantly correlated with random blood sugar and blood pressure level. Whereas gender was significantly correlated to the RBS level, while negatively correlated to blood pressure level. Even though the economic status was not significant, educational status was significant to both RBS and blood pressure level. Conclusion: This inquest portrayed that educational stature brings out an immense reverberation on glycemic and blood pressure control apart from other demographic variables. So this study confers an insight that, strategies for educating patients especially in rural areas thereby making them aware of long-term complications leads to augment overall health outcome.